Development of a Liquid‐Liquid Biphasic Reaction Using a Taylor Vortex Flow Reactor. Issue 6 (11th May 2021) - Hosoya, Masahiro; Manaka, Atsushi; Nishijima, Shogo; Tsuno, Naoki
Abstract: This paper describes a liquid‐liquid biphasic flow reaction system that is simple to control. In a liquid‐liquid biphasic flow reaction, the slug‐flow in the tube reactors generally improves the reaction rate. However, we show that larger tube diameters decreased the reaction rate and the formation of the slug‐flow was influenced by the tube diameter, the size of the mixer, and the pump mechanism. These results indicated that technical difficulties with the slug‐flow could be an obstacle to scale‐up. To resolve this problem, we suggest the use of a Taylor vortex flow reactor to achieve a higher reaction rate than with batch and slug‐flow systems. Abstract : A Taylor vortex flow reactor showed higher conversion compared to the batch and slug‐flow conditions in liquid‐liquid biphasic reaction. This flow reactor has a simple structure, which consists of a cylindrical tube and a rotation axis. Also, this methodology is potentially suitable for the scale‐up under continuous flow conditions.